SARS-CoV-2-Specific Antibody Prevalence and Symptoms in a Local Austrian Population - Ladage, Dennis; Höglinger, Yana; Ladage, Dorothee; Adler, Christoph; Yalcin, Israfil; Harzer, Oliver; Braun, Ralf J. (Frontiers in Medicine, 2021)
Background: Since December 2019 SARS-CoV-2 is the center of global attention due to its rapid transmission and toll on health care systems and global economy. Population-based serosurveys measuring antibodies for SARS-CoV-2 provide one method for estimating previous infection rates including the symptom-free courses of disease and monitoring progression of the epidemic. Methods: In June 2020 we succeeded in testing almost half of the population of an Austrian township (n=835 of 1359 inhabitants) with a reported higher incidence for COVID-19 infections (17 PCR positive cases have been officially reported until the date of sample collection, i.e., 1.2% of the total population). We determined the prevalence of SARS-CoV-2-specific antibodies in this population, factors affecting, and symptoms correlated with prior infection. Antibodies were determined using a CE-certified quality-controlled ELISA test for SARS-CoV-2-specific IgG and IgA antibodies. Results: We found a high prevalence of 9% positive antibodies among the town population in comparison to 6% of the neighboring villages. This was considerably higher than the officially known RT-PCR-approved COVID-19 cases (1.2%) in the town population. 20% of SARS-CoV-2-antibody positive cases declared being asymptomatic in a questionnaire. On the other hand, we identified six single major symptoms, including anosmia/ageusia, weight loss, anorexia, general debility, dyspnea, and fever, and especially their combination to be of high prognostic value for predicting SARS-CoV-2 infection in a patient. Conclusions: This population study demonstrated a high prevalence of antibodies to SARS-CoV-2 as a marker of past infections in an Austrian township. Several symptoms revealed a diagnostic value especially in combination.